Distribution of cardiovascular disease risk according to SCORE2 and potential need for cholesterol and blood pressure lowering therapy in apparently healthy middle-aged individuals. (3rd October 2022) - Yari, A; Ueda, P; Hagstrom, E; Lundman, P; Ravn-Fischer, A; Soderberg, S; Yndigegn, T; Jernberg, T
Abstract: Background: The 2021 European Society of Cardiology (ESC) prevention guidelines recommend the Systemic Coronary Risk Estimation 2 algorithm (SCORE2) to estimate the 10-year risk of cardiovascular disease (CVD) events to guide pharmacological treatment for primary prevention in apparently healthy individuals aged 40–69 years. Purpose: To assess the distribution of CVD risk according to SCORE2 and the proportion of individuals who could be eligible for pharmacological treatment of blood cholesterol and blood pressure in an apparently healthy middle-aged population in Sweden. Methods: We used data from the Swedish Cardiopulmonary Bioimage Study (SCAPIS) which used population registers to randomly recruit individuals aged 50–64 years at six Swedish study sites. Information was collected from the study participants through clinical examinations, national registries, and questionnaires. We excluded individuals with previously known atherosclerotic CVD, diabetes mellitus, or chronic kidney disease with eGFR <60 mL/min/1.73 m 2 . The SCORE2 algorithm designed for countries with moderate baseline CVD risk was used to categorize study participants' 10-year CVD risk as low-moderate (<5% risk); high (5-<10% risk); and very-high (≥10% risk). The proportions of the population who could be eligible, according to the 2021 ESC prevention guidelines, for pharmacological treatment of LDL-cholesterol (LDL-C) were assessed. Treatment thresholds for LDL-C according to SCORE2 risk were ≥1.8 mmol/L (high risk) and ≥1.4 mmol/L (very-high risk). Treatment threshold for hypertension was defined as a blood pressure ≥140/90 mmHg regardless of CVD risk. Results: SCAPIS included 30, 082 individuals. After exclusion criteria were applied 26, 877 individuals remained (median age 57.2 years; 52.8% women). The median 10-year risk of CVD according to SCORE2 was 5.0 (interquartile range 3.0, 7.0) %. In total, 47.5% were classified as low-moderate risk, 45.9% as high risk, and 6.6% as very-high risk, with men having higher risk than women (figure). Almost all of those with high and very-high risk had LDL-C levels above the treatment thresholds. As such, according to the guidelines, lipid-lowering treatment should be considered (high risk) or was generally recommended (very-high risk) in 51.7% of the total population (Figure 1). The proportion of individuals with blood pressure ≥140/90 mmHg was 21.9%. The self-reported use of lipid-lowering therapy among low-moderate, high risk, and very-high risk individuals was 3.1%, 6.9%, and 6.3%, respectively. The use of blood pressure lowering therapy was 13.1% for those with blood pressure <140/80 mmHg and 29.2% for those ≥140/90 mmHg. Conclusions: In this population-based study of nearly 27, 000 apparently healthy middle-aged individuals in Sweden, around half of the individuals could be eligible for LDL-C-lowering therapy and around one in five could be eligible for antihypertensive therapy according to the 2021 ESC prevention guidelines. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): SCAPIS funding: The Swedish Heart-Lung Foundation and Knut and Alice Wallenberg Foundation.